E-Commerce Logistics Integration for Sustainable Agricultural Value Chains Toward a Digital Green Supply System - Hajar, Dewi (Professorline, 2025)
The rapid expansion of e-commerce logistics has transformed agricultural value chains, creating new opportunities for efficiency, traceability, and sustainability. However, the integration of logistics systems with sustainable agriculture remains limited in both practice and policy. This study develops a conceptual framework called the Digital Green Supply System (DGSS) by extending the model proposed by Zhou et al. (2024) on optimal logistics strategies for green agricultural e-commerce. Using a theory-extension approach based on secondary quantitative findings and system-level interpretation, the research explores how digital logistics can serve as a catalyst for sustainable agricultural transformation. The analysis reinterprets key parameters game-theoretic model logistics service cost coefficient (k), consumer sensitivity to logistics quality (γ), and platform commission rate (ρ) to explain how cost–service trade-offs influence environmental and economic outcomes. The proposed DGSS framework comprises four interconnected layers: digital integration, green logistics, value chain optimization, and sustainability feedback. Together, these components form an adaptive ecosystem that balances profitability, carbon efficiency, and social inclusivity through data-driven coordination and real-time feedback loops. The findings highlight that e-commerce logistics integration can reduce post-harvest losses, lower emissions, and enhance market accessibility for rural producers. Policy implications include promoting green logistics subsidies, digital infrastructure investment, and open data systems to strengthen environmental accountability. Overall, the DGSS framework positions e-commerce logistics as both a strategic enabler of sustainable agriculture and a foundation for low-carbon, resilient, and inclusive agri-food systems.